Pengenalan Bahasa Jepang Melalui Kertas Bergambar Untuk Siswa Pasraman Widya Segara Nusa - Dewi, Ni Putu Sasmika; Jelantik, I Wayan Aria (IAHN Gde Pudja Mataram, 2023)
Tourism is a travel activity to find peace and comfort. The purpose of tourism is not merely to places full of interesting attractions or trending places, nowadays many tourists travel to heal themselves or strengthen their faith. Pasraman as one of the places of Hindu Religious Education is now starting to switch functions to become a religious tourist spot that attracts foreign tourists with its activities such as tirtayatra, yoga, and natural healing. For this reason, Pasraman must be ready to improve the quality of its students with various skills, one of which is Japanese. This five-day community service took place at Pasraman Widya Segara, Mekar Sari Hamlet, Batu Leong, West Sekotong, where this location has considerable tourism potential. While the purpose of this activity is to introduce Japanese language to Pasraman Widya Segara Nusa students through illustrated paper. With training and mentoring methods, the material presented is made as interesting as possible. The materials provided are simple Japanese materials related to the field of tourism such as place names, names of food and drinks, directions, names of transportation equipment and greetings. As a result, the pasraman students were enthusiastically and confidently able to practice what they had learned and also pronounce Japanese vocabulary properly.